Living Collections of Threatened Plants in Botanic Gardens: When Is Ex Situ Cultivation Less Appropriate than Quasi In Situ Cultivation? - Sergei Volis (Journal of Zoological and Botanical Gardens, 2023)
Botanic gardens play an increasingly important role in the conservation of global biodiversity. However, although botanical gardens periodically report the results of introducing certain species of native flora, they rarely attempt to summarize existing knowledge to make general recommendations regarding ex situ collections. The aim of this study was to analyze the many years of experience of the Tashkent Botanical Garden in creating and maintaining living collections of threatened species of Uzbekistan (the majority of which are endemic to the country or Central Asia) in order to identify species whose cultivation ex situ is advisable, and whose cultivation will not result in meaningful conservation. Careful analysis of the species introduction history revealed that a simple dichotomy of the introduction results (success/failure) appears to be an oversimplification. In terms of the cultivation success, the introduced plant species can rather be classified into three categories: success, failure, and dubious success. For many species whose introduction was earlier considered successful, the introduction success is questionable and further efforts to conserve these species ex situ should be abandoned. A decision tree and classification of threatened perennials for possible ex situ introduction are proposed and the species in TBG collections are tabulated according to the latter. Species considered unsuitable for ex situ conservation are recommended for quasi in situ conservation. Both approaches, ex situ and quasi in situ, should be intensively used as a part of an integral conservation strategy for preserving plant biodiversity.